Crystallization and self-assembly of shape-complementary sequence-defined peptoids. Issue 33 (1st June 2021) - Xuan, Sunting; Jiang, Xi; Balsara, Nitash P.; Zuckermann, Ronald N.
Abstract : Shape complementarity between polymers is a hallmark of biological systems ( e.g. DNA base pairing and protein binding interactions). Here we explore the role of shape complementarity between sequence-defined  N -alkyl peptoids in crystal lattices. Abstract : The universal pairing of complementary nucleobases in DNA found in all life forms has inspired extensive studies on selective molecular recognition between information-rich sequence-defined polymer chains. Here we utilized the shape complementarity of sequence-defined peptoids to achieve selective assembly between peptoid chains. Three sets of self-complementary peptoids bearing different overall molecular shapes, determined by the monomer sequence (trapezoid, comb and zig-zag), were synthesized and systematically studied by differential scanning calorimetry and X-ray diffraction. All these peptoids crystallized in bulk into a nearly identical rectangular crystal lattice as evidenced by their similar melting temperatures and X-ray diffraction peaks. In aqueous solution, they all self-assembled into crystalline monolayer nanosheets with a known rectangular crystal lattice motif, regardless of their varied molecular shapes. These results suggest that complementary molecular shape could be a potential design element for the construction of more sophisticated, hierarchically-ordered peptoid nanomaterials that approach the structural and functional complexity found in biomacromolecular nanostructure.